2002
DOI: 10.1002/jms.296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a ring substituent on the tendency to form H2O adducts to Ag+ complexes with phenylalanine analogues in an ion trap mass spectrometer

Abstract: In a previous report we showed that certain binary Ag(+)-amino acid complexes formed adduct ions by the attachment of a single water and methanol molecule when stored in an ion trap mass spectrometer: complexes with aliphatic amino acids and with 4-fluorophenylalanine formed the adduct ions whereas complexes with phenylalanine and tryptophan did not. In this study we compared the tendency of the Ag(+) complexes derived from phenylalanine, 4-fluorophenylalanine, 4-hydroxyphenylalanine (tyrosine), 4-bromophenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…The trend indicates that as the charge on the metal decreases the reactivity of the complex decreases. This result is not surprising, and it agrees with our previous report [18] and the work of others [48,49] in which the ability of the ligand donor groups to donate electron density to the metal center was observed to directly affect complex reactivity. Essentially, greater metal-donor overlap, which leads to stronger metal-ligand bonds, decreases the charge on the metal and weakens the metal-CH 3 CN interaction, which leads to lower equilibrium constants.…”
Section: Chelate Ring Size Effectssupporting
confidence: 93%
“…The trend indicates that as the charge on the metal decreases the reactivity of the complex decreases. This result is not surprising, and it agrees with our previous report [18] and the work of others [48,49] in which the ability of the ligand donor groups to donate electron density to the metal center was observed to directly affect complex reactivity. Essentially, greater metal-donor overlap, which leads to stronger metal-ligand bonds, decreases the charge on the metal and weakens the metal-CH 3 CN interaction, which leads to lower equilibrium constants.…”
Section: Chelate Ring Size Effectssupporting
confidence: 93%
“…During the isolation step, all ionized species except the one chosen for storage are resonantly ejected from the ion trap. The appearance of peaks 18 u higher than the isolated ion is indicative of the formation of H 2 O adducts [23][24][25]; the abundance of the adducts increased as the isolation and storage time was extended. The formation of abundant H 2 O adducts indicates that several of the uranyl complex ions show a significant tendency to accept ligands via gas-phase association reactions in the ion trap.…”
Section: Resultsmentioning
confidence: 99%
“…To gain a better understanding of the intrinsic interactions between different uranyl species and solvent, we have begun an investigation of uranyl-anion complexes in the gas phase using ion-trap mass spectrometry (IT-MS). Several recent reports have demonstrated that intrinsic metal and metal complex chemistry can be investigated by the (controlled) addition of reagent gas to an ion trap [12][13][14][15][16][17][18][19][20][21][22], or by way of the presence of H 2 O and other small molecule contaminants within the He bath gas used to collisionally cool ions and improve trapping efficiency [23][24][25]. The reactions of uranium ions in the gas phase have been the subject of several earlier investigations.…”
mentioning
confidence: 99%
“…ESI-MS, multiple-stage CID and ion-molecule reactions were carried out using established procedures described elsewhere [22,24,26]. Briefly, ESI mass spectra were collected using a Finnigan LCQ-Deca ion-trap mass spectrometer (ThermoFinnigan Corporation, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
“…To gain a better understanding of the intrinsic interactions between different uranium species and solvent, we have turned to investigations of uranyl-anion complexes in the gas phase. Recent studies have shown that ion-trap mass spectrometry can be used to probe intrinsic metal and metal-complex chemistry by exposing metal species to reagent gases deliberately added to the ion trap [9 -20], or to adventitious H 2 O present in the He bath gas used to collisionally cool ions and improve trapping efficiency [21][22][23][24]. Further motivating the present study is the fact that ion traps will shortly be used to characterize actinide speciation in samples from radioactive waste disposal sites, and a concise understanding of actinide behavior will be critical for correctly interpreting environmental data [25].…”
mentioning
confidence: 99%